Complex Positive Effects of SGLT-2 Inhibitor Empagliflozin in the Liver, Kidney and Adipose Tissue of Hereditary Hypertriglyceridemic Rats: Possible Contribution of Attenuation of Cell Senescence and Oxidative Stress - Trnovska, Jaroslava; Svoboda, Petr; Pelantova, Helena; Kuzma, Marek; Kratochvilova, Helena; Kasperova, Barbora Judita; Dvorakova, Iveta; Rosolova, Katerina; Malinska, Hana; Huttl, Martina; Markova, Irena; Oliyarnyk, Olena; et al. (International journal of molecular sciences, 2021)
(1) Background: empagliflozin, sodium-glucose co-transporter 2 (SGLT-2) inhibitor, is an effective antidiabetic agent with strong cardio- and nephroprotective properties. The mechanisms behind its cardio- and nephroprotection are still not fully clarified. (2) Methods: we used male hereditary hypertriglyceridemic (hHTG) rats, a non-obese model of dyslipidaemia, insulin resistance, and endothelial dysfunction fed standard diet with or without empagliflozin for six weeks to explore the molecular mechanisms of empagliflozin effects. Nuclear magnetic resonance (NMR)-based metabolomics; quantitative PCR of relevant genes involved in lipid and glucose metabolism, or senescence; glucose and palmitic acid oxidation in isolated tissues and cell lines of adipocytes and hepatocytes were used. (3) Results: empagliflozin inhibited weight gain and decreased adipose tissue weight, fasting blood glucose, and triglycerides and increased HDL-cholesterol. It also improved insulin sensitivity in white fat. NMR spectroscopy identified higher plasma concentrations of ketone bodies, ketogenic amino acid leucine and decreased levels of pyruvate and alanine. In the liver, adipose tissue and kidney, empagliflozin up-regulated expression of genes involved in gluconeogenesis and down-regulated expression of genes involved in lipogenesis along with reduction of markers of inflammation, oxidative stress and cell senescence. (4) Conclusion: multiple positive effects of empagliflozin, including reduced cell senescence and oxidative stress, could contribute to its long-term cardio- and nephroprotective actions.
Keywords: buňky 3T3-L1; Liver; Animals; Kidney; Hep G2 Cells; Rats; Sodium-Glucose Transporter 2 Inhibitors; Glucosides; metabolic syndrome; lipogeneze; buňky Hep G2; hmotnostní přírůstek; oxidační stres; játra; empagliflozin; Dyslipidemias; výsledek terapie; Weight Gain; Up-Regulation; glukosidy; benzhydrylové sloučeniny; insulin sensitivity; Oxidative Stress; Gluconeogenesis; lidé; stárnutí buněk; Mice; Hypoglycemic Agents; upregulace; cell senescence; Treatment Outcome; myši; glukoneogeneze; Humans; hypoglykemika; Down-Regulation; Benzhydryl Compounds; 3T3-L1 Cells; Male; hereditary hypertriglyceridemic rat model; modely nemocí na zvířatech; aplikace orální; Insulin Resistance; dyslipidemie; inzulinová rezistence; Disease Models, Animal; krysa rodu Rattus; Hypertriglyceridemia; Lipogenesis; hypertriglyceridemia; down regulace; Administration, Oral; zvířata; tuková tkáň; viabilita buněk; mužské pohlaví; Cell Survival; ledviny; Cellular Senescence; glifloziny; hypertriglyceridemie; Adipose Tissue